FPGA implementation and evaluation of synchronization architectures for ethernet-based cloud-ran fronthaul - FREIRE, Igor Antonio Auad (Universidade Federal do Pará, 2017)
The use of Ethernet infrastructure available in most commercial buildings can alleviate the costs involved with fronthaul provisioning in cloud radio access networks. However, current fronthaul specifications rely on dedicated synchronous links, which natively support features such as accurate synchronization across radio devices. In this context, a cost-effective and backwardscompatible solution is to adapt standard fronthaul interfaces (e.g. CPRI) to asynchronous networks by using endpoint equipments capable of meeting synchronization requirements over legacy Ethernet. This dissertation proposes design considerations for synchronization of radio over Ethernet and evaluates the feasibility of synchronization architectures by developing an FPGA-based hardware testbed. It contrasts two solutions, a simplistic approach that employs elastic buffering for recovering frequency and an end-to-end IEEE 1588 Precision Time Protocol solution for time and frequency alignment. Results suggest that the scheme with PTP solely at the endpoints can comply with time and frequency alignment requirements of current mobile standards if packet delay variation is treated with sound algorithms.